Caracterização molecular de cepas do vírus respiratório sincicial isoladas de casos de infecção respiratória aguda na cidade de Belém, Pará, Brasil nos anos de 2000 a 2006 - SANTOS, Mirleide Cordeiro dos (Universidade Federal do Pará, 2013)
The diseases of respiratory tract are the main complaints in the services of medical consultations, acute respiratory infections (ARI) are the most common manifestations, mainly in children under five years old. In developing countries ARI represent a serious problem of public health. Every year, ARI are responsible by about 2 million deaths all over the world. Among the infectious agents the Respiratory Syncytial virus (RSV) is the most important pathogen in infants and young children because of severe bronchiolitis and pneumonia that it may cause. With the objective to generate data on the molecular epidemiology of this virus, patients' clinical samples with ARI were analyzed during the period 2000 - 2006 in the city of Belém, Pará. Test of Indirect immunofluorescence (TIF) was used for antigenic characterization of isolated viruses and the RT-PCR for the genes encoders of the proteins G and F, that were partially sequenced. In the total period, 153 positive samples of RSV were analyzed. The age group 0-4 years showed the larger number of cases (90,19%). In relation to the seasonal profile, the pick of activity of RSV happened in the first six months of the year, being associated mainly to the period of change of the rainy season to a less rainy period. There was a co-circulation of the subgroups A and B in the years of 2001 and 2003. In 2000, 2005 and 2006 just the subgroup A was detected. However in the year of 2004 was only registered the occurrence of subgroup B. Inside the studied period, were detected different genotypes from the protein G of the subgroup A (GA2 and GA5) and of the subgroup B (SAB1 and SAB3) , indicating the first report about circulation of the genotype SAB1 in South America. In 2004, was found a differentiated cluster of the other circulating genotypes, being denominated BRB1. The analysis from gene encoder of the protein F allowed identification of mutations in the nucleotidic sequence that resulted in changes in the aminoacídica chain. This study represents the first report about the molecular epidemiology of the Respiratory Syncytial Virus in the North region of Brazil.